Analysis of Cross-Sectoral Collaboration in Local Disaster Management: A Study on the Bima Regency Government - Ishaka, Mukhlis; Kadir, Abdul; Haeril, Haeril; Suraya, Suraya; Irawansyah, Irawansyah (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study aims to determine cross-sectoral collaboration efforts in disaster management in Bima Regency through coordination, integration, partnership, and empowerment. The subjects of this study were selected through a purposive sampling technique. Data collection techniques consist of observation, interviews, and documentation. The results of the study indicate that the implementation of disaster management, apart from referring to the ability of the Regional Government of Bima Regency to implement policies and their performance effectively, also applies the principles of integration and various levels of organization. Especially in disaster prevention and mitigation efforts, the Regional Government of Bima Regency collaboratively seeks to strengthen rules and institutional capacity and disseminate regulations and guidelines for implementing the Bima Regency Spatial Plan by implementing building zoning in disaster risk areas. Then carry out Research and Development activities involving professional Research Teams and NGOs. Publish research results to be used as guidelines for reducing risk and increasing knowledge of the government and the community in efforts to reduce disaster risk.